Nursing Students Explore Meaningful Activities for Nursing Home Residents: Enlivening the Residents by Cultivating Their Spark of Life - Britt Øvrebø Haugland; Tove Giske (MDPI AG, 2021)
International research focuses on person-centered care, quality of life, and quality of care for people living in long-term care facilities, and that it can be challenging to improve the quality of life for residents with dementia. The aim of this study was to explore ways of developing appropriate person-centered activities for nursing home residents based on what would be meaningful for them. A qualitative explorative design was chosen. Twelve students each year over a three-year period participated in the study (altogether 36). Each student tailored joyful and meaningful activities for two nursing home residents and wrote eight reflection journals each (altogether 284). Additional data came from eight focus group interviews with the students. Data were analyzed using qualitative content analysis. The main theme was "Enlivening the residents by cultivating their spark of life". Two main categories were identified: (1) "Journeying to meaningful and enlivening (enjoyable) activities", and (2) "Expressions of enlivening", It is possible to tailor meaningful and enlivening activities together with the individual person with dementia. Involvement and engagement are necessary to understand the verbal and nonverbal expressions and communicate with the individual resident.